Clinico-epidemiological Profile of Pneumonia in Patients with Chronic Obstructive Pulmonary Disease - Koirala, Puru; Mehta, Ram Kumar; Gautam, Sakshyam; Khan, Sajjad Ahmed; Parajuli, Surya B. (Nepal Journal of Medical Sciences, 2024)
Introduction: Chronic obstructive pulmonary disease (COPD) is a common cause of morbidity and mortality in the adult population, with a high burden in Nepal. Pneumonia is a common cause of COPD exacerbations. The study aimed to determine the clinico-epidemiologic characteristics of pneumonia in COPD patients. Methods: This hospital-based, cross-sectional study was conducted at Birat Medical College Teaching Hospital, using a structured proforma that recorded patient sociodemography, clinical history, examination, and laboratory data. The pneumonia severity was documented using the Pneumonia Severity Index (PSI) score and CURB-65 score. Results: Out of a total of 152 COPD patients with pneumonia, there were 84 (55.26%) patients with atypical pneumonia and 68 (44.74%) with typical pneumonia, 107(70.39%) had a smoking history, dyspnea was present in 75 (58.59%) atypical pneumonia patients and 53 (41.41%) typical pneumonia patients. Respiratory failure was present in 130 (85.53%), and 30 (19.74%) patients had altered sensorium. Patients admitted to ICU were 106 (69.74%), with 57 (53.77%) classed PSI IV and 31 (29.25%) as PSI Class V. CURB-65 score of  3 had sensitivity of 23.9%, specificity of 94.4%, positive predictive value of 97% and a negative predictive value of 14.3% in predicting need for ICU admission. Conclusions: COPD patients with pneumonia commonly present with atypical pneumonia, have chronic co-morbidities, and have high PSI classification on admission. The PSI is preferred over CURB-65 score in predicting ICU admission.